2011
DOI: 10.3109/09637486.2011.634785
|View full text |Cite
|
Sign up to set email alerts
|

Milk from cows of different β-casein genotypes as a source of β-casomorphin-7

Abstract: The aim of this study was to quantify β-casomorphin-7 in raw, hydrolyzed and processed milk in different stages of the cow lactation. The obtained results lead to the following conclusion: the highest amount of β-casomorphin-7 released from the hydrolyzed and processed milk is related to the β-casein A1 allele, irrespective of a lactation period. Some traces of β-casomorphin-7 in milk from cows with the β-casein A2 variant are probably a result of the acid hydrolysis of β-casein during its digestion with pepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 28 publications
4
49
0
4
Order By: Relevance
“…One alternative method for BCMs determination is ELISA (Sienkiewicz-Sz»apka et al, 2009;Cieslinska et al, 2012). Using ELISA, levels of BCM7 and BCM5 in cheese as low as 0.04 and 0.05 mg/g, respectively, could be accurately quantified.…”
Section: Microlc-tof-msmentioning
confidence: 99%
See 4 more Smart Citations
“…One alternative method for BCMs determination is ELISA (Sienkiewicz-Sz»apka et al, 2009;Cieslinska et al, 2012). Using ELISA, levels of BCM7 and BCM5 in cheese as low as 0.04 and 0.05 mg/g, respectively, could be accurately quantified.…”
Section: Microlc-tof-msmentioning
confidence: 99%
“…So high levels of somatic cell may degrade BCM7; but this needs further investigation. Similarly, Cieslinska et al (2012) investigated the presence of BCM7 in bovine milk collected from healthy cows which did not indicate any subclinical symptom of mastitis and showed that BCM7 was detected in all milk samples with the highest amount in A1 milk, followed by A1A2 milk and A2 milk. Surprisingly, BCM7 was found in the milk containing the A1 variant but also in A2 variant-containing milk.…”
Section: Presence Of Beta-casomorphins In Dairy Products Milkmentioning
confidence: 99%
See 3 more Smart Citations